1999
DOI: 10.1152/ajplung.1999.276.4.l582
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of adherens junctions by transforming growth factor-β1: role of contraction

Abstract: The signal transduction pathways that lead to disruption of pulmonary endothelial monolayer integrity by transforming growth factor-β1 (TGF-β1) have not been elucidated. The purpose of this investigation was to determine whether disassembly of the adherens junction is temporally associated with the TGF-β1-induced decrease in pulmonary endothelial monolayer integrity. Measurement of albumin clearance and electrical resistance showed that monolayer integrity started to decrease between 1 and 2 h post-TGF-β1 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 38 publications
7
90
0
Order By: Relevance
“…Indeed, the treatment of HUVECs with TGF-b1 resulted in significant exposure of the subendothelial matrix. This result is corroborated by the work of others, who demonstrated that TGF-b1 promotes a strong rearrangement of endothelial adherent junctions and actin cytoskeleton, resulting in increased areas of cell separation (Goldblum et al, 1999;Hurst et treated or not with 10 ng TGF-b1 ml "1 for 4 h, were pre-incubated with polyclonal anti-FN antibodies or rabbit control IgGs (both at 10 mg ml "1 ), or with an anti-LM serum or a pre-immune serum (both at 1 : 1000). Then cultures were incubated with S. schenckii yeasts (5¾10 6 cells) for 90 min.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Indeed, the treatment of HUVECs with TGF-b1 resulted in significant exposure of the subendothelial matrix. This result is corroborated by the work of others, who demonstrated that TGF-b1 promotes a strong rearrangement of endothelial adherent junctions and actin cytoskeleton, resulting in increased areas of cell separation (Goldblum et al, 1999;Hurst et treated or not with 10 ng TGF-b1 ml "1 for 4 h, were pre-incubated with polyclonal anti-FN antibodies or rabbit control IgGs (both at 10 mg ml "1 ), or with an anti-LM serum or a pre-immune serum (both at 1 : 1000). Then cultures were incubated with S. schenckii yeasts (5¾10 6 cells) for 90 min.…”
Section: Discussionsupporting
confidence: 74%
“…It has been suggested that actin cortical patches may be essential for the initiation of endocytosis (EngqvistGoldstein & Drubin, 2003). Interestingly, treatment of HUVECs with TGF-b1 induced a modification in the microfilament cytoskeleton structure, leading to an actin rearrangement from a cortical pattern to an array of perpendicular stress fibres, as already described by others (Goldblum et al, 1999;Hurst et al, 1999).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…First, the concentration of TGF-␤1 is elevated in edema fluid from patients with acute lung injury (18), and active TGF-␤1 is present early in the syndrome, detectable within 24 h of initial diagnosis (19). TGF-␤1 has been associated with increased endothelial and epithelial permeability, leading to pulmonary edema (20,21). We have also shown that increased TGF-␤1 activity in the distal airspaces during ALI promotes alveolar edema by reducing distal airspace epi-thelial sodium and fluid clearance.…”
Section: Acute Lung Injury (Ali)mentioning
confidence: 99%
“…It was reported that rearrangement of expression of VE-cadherin, the transmembrane protein for the formation of adherens junction, occurred under shear conditions (14) . Furthermore, tumor necrosis factor-α (TNF-α) (15) and TGF-ß1 (16) , which are synthesized by SMCs, have effects on expression of VEcadherin. For quantitative analysis of EC permeability, well-defined flow conditions and cellular interactions between ECs and SMCs are necessary.…”
Section: Introductionmentioning
confidence: 99%